(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Upper cross syndrome has become prevalent in today’s population. This syndrome refers to tightness of muscles such as pectoralis major, upper trapezius and levator scapulae and weakness of deep neck flexors, scalene, rombhoids, serratus anterior, middle and lower trapezius. Poor posture is associated with imbalance created in musculoskeletal system and common condition to be reported as upper cross syndrome. It is commonly seen in people with forward head posture, desk job workers, dentist, beauticians etc. The resulting clinical presentation is complaint of pain in neck and shoulder, cervicogenic headache, hunched upper-back and rounded shoulder. Children are not as proactive today and the rate of the Upper cross syndrome is on the rise. This deviated posture and sedentary lifestyle continues, where it progresses more as the age progresses in adulthood. Aims and objectives: To screen, detect, early treat as well as prevent upper cross syndrome in young individuals. Materials and methods: Asymptomatic individual with 20-40 years of age group will be explained about the procedure before commencement of the study. Posture will be screened using Kinect Azure and REEDCO Posture Assessment Scale will be used for evaluation. Assessment of muscle tightness and weakness will be evaluated using muscle length tests and manual muscle testing. Results: The expected results would include details about prevalence of UCS in asymptomatic individual. The parameters of outcome measures will be analyzed using the statistical test namely students paired T-test. Conclusion: Based on previous data we assume it is essential to screen asymptomatic individual to looks for signs of Upper Cross Syndrome for early detection, prevention and treatment.